Acting Independently While Living Alone: The Strategies and Struggles of Cancer Patients. (August 2015) - Benoot, Charlotte; Deschepper, Reginald; Grypdonck, Maria; Saelaert, Marlies; Bilsen, Johan
Cancer patients who live alone place specific importance on acting independently during treatment. We want to describe what it means to act independently and which strategies patients use to continue to act independently. We used a qualitative design, based on grounded theory. We interviewed 32 patients, 17 of them a second time. Patients who live alone defined acting independently in two different ways: It meant not only doing things alone but also using the help of others in a controlled way. These two meanings lead to two types of strategies. As treatment evolves, patients needed to change their preferred type of strategies to continue acting independently. Succeeding to change led to a feeling of mastery and success. However, failing to change led to struggling, whereby patients' needs became invisible. Health care providers should anticipate patients' inability to change strategies during cancer treatment, thereby preventing the patient's struggle from only becoming visible during crisis.